Kinerja Pegawai Ditinjau Dari Aspek Kemampuan Intelektual dan Disiplin Kerja Pada Kantor Kecamatan Siantar Sitalasari Kota Pematangsiantar - Grace Endang Pakpahan; Dita Permata Sari; Novita Butarbutar (Jurnal Manajemen dan Bisnis, 2020)
ABSTRACTThe purpose of this study are to determine the influence of intellectual ability and work decipline on employee performance at Kantor Kecamatan Siantar Sitalasari Kota Pematangsiantar. The research was done by using the design of library and field research. The research method used is the causality method with a qualitative and quantitative approach. The sources of data used in this research are primary and secondary. The population in this study were all employee which amounted to 46 employees. The datawere collected through questionnaire, interviews and documentation.  The analysis technique used is qualitative and descriptive quantitative analysis which consists of multiple linear regression, correlation test and test of determination and hypothesis. Theresults of this study can be summarized are the intellectual ability, the work discipline and the employee performance are good. Then the intellectual ability have a positive and significant influence to the employee performance. Next work descipline have a positive and significant influence to the employee performance.